Ultrasound elastography for carpal tunnel pressure measurement: A cadaveric validation study. Issue 1 (14th August 2017) - Kubo, Kazutoshi; Zhou, Boran; Cheng, Yu‐Shiuan; Yang, Tai‐Hua; Qiang, Bo; An, Kai‐Nan; Moran, Steven L.; Amadio, Peter C.; Zhang, Xiaoming; Zhao, Chunfeng
ABSTRACT: Carpal tunnel pressure is a key factor in the etiology of carpal tunnel syndrome. Numerous approaches have been conducted to measure carpal tunnel pressure. However, most techniques are invasive and take time and effort. We have developed an innovative approach to noninvasively assess the tunnel pressure by using the ultrasound surface wave elastography (USWE) technique. In a previous study it was shown that the shear wave speed in a tendon increased linearly with increasing tunnel pressure enclosed the tendon in a simple tendon model. This study aimed to examine the relationship between the carpal tunnel pressure and the shear wave speeds inside and outside the carpal tunnel in a human cadaveric model. The result showed that the shear wave speed inside the carpal tunnel increased linearly with created carpal tunnel pressure, while the shear wave speed outside the carpal tunnel remained constant. These findings suggest that noninvasive measurement of carpal tunnel pressure is possible by measuring the shear wave speed in the tendon. After fully establishing this technology and being applicable in clinic, it would be useful in the diagnosis of carpal tunnel syndrome. For that reason, further validation with this technique in both healthy controls and patients with carpal tunnel syndrome is required. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:477–483, 2018. Abstract : For the purpose of deducing the carpal tunnel pressure noninvasively, this study was conducted to evaluate the relationship between the carpal tunnel pressure and the shear wave speeds propagating the tendon inside and outside the carpal tunnel in a human cadaveric model by using the ultrasound surface wave elastography technique. The result showed that the shear wave speed inside the carpal tunnel increased linearly with created carpal tunnel pressure, while the shear wave speed outside the carpal tunnel remained constant.